If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -10 = -50 Reorder the terms: -10 + 4m = -50 Solving -10 + 4m = -50 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4m = -50 + 10 Combine like terms: -10 + 10 = 0 0 + 4m = -50 + 10 4m = -50 + 10 Combine like terms: -50 + 10 = -40 4m = -40 Divide each side by '4'. m = -10 Simplifying m = -10
| 2n+2n=20 | | 2n+2n=24-2n | | n+n=24-2n | | 4m-10=30 | | 157-7x=29x+21 | | 157-7x=28x+21 | | n/2=46-19 | | n*2=46-19 | | n+11=36-12 | | n*11=36-12 | | n/2=50-24 | | n+12=43-17 | | n*2=63-7 | | x*3+9=37+x | | n*2=70 | | 3/3+4/4 | | 33=(m-5)*m | | v/5=3 | | 441+659=v | | 677+n=896 | | n-7=48 | | 719+n=803 | | n-8=32 | | n/4 | | 9*(-7)+3+7=x | | -8+3*5+2=x | | 1-4-5*2=x | | 7*8-9+4=x | | -9(x-7)=3(x-5) | | 6=-16t^2+30t+15 | | -3-1*3-8=x | | -6-7*6*5=x |